Efeitos do tratamento com alisquireno e L-arginina sobre a sensibilidade barorreflexa e estresse oxidativo de ratos com hipertensão renovascular - Mengal, Vinícius (2015)
Renovascular hypertension is characterized by increased angiotensin II, oxidative stress, and by endothelial dysfunction. The purpose of this study was tested if the administration of aliskiren (ALSK) and L-arginine (L-ARG), would restore impaired baroreflex sensitivity and reduce the oxidative stress in a rat renovascular hypertension model. Hypertension was induced by clipping the left renal artery, and the following 5 groups were divided: SHAM, 2-kidney, 1-clip (2K1C); 2K1C plus ALSK (ALSK); 2K1C plus L-ARG (L-ARG); and 2K1C plus ALSK+ L-ARG (ALSK+LARG). SOD-2 and Catalase expression was measured in plasma and tissues and Assay of advanced oxidation protein products. After 21 days of treatment, only the ALSK+L-ARG group was effective in normalize the arterial pressure ( 108.8±2.8 mmHg). The L-ARG and ALSK+L-ARG groups not show hypertrophy of the left ventricle. All treatments restored the depressed baroreflex sensitivity to values found by SHAM group in both parasympathetic and sympathetic component of baroreflex system. Acute administration of TEMPOL restored the depressed baroreflex sensitivity in 2K1C group to values that resembles to those presented by other groups. The advanced oxidation protein products levels in plasma that 2K1C group was significantly increased in 2K1C group compared with SHAM, ALSK, L-ARG and ALSK+L-ARG groups (5,79±0,67 vs. 3,79±0,41; 3,96±0,35; 4,26±0,47 and 3,91±0,36 umol/Lchloramine-T respectively, P<0.05). The similar responses was found in cardiac tissue. The SOD-2 and Catalase expression in the cardiac tissue was significantly increased in ALSK, L-ARG and ALSK+L-ARG. The gp91phox in the cardiac tissue to L-ARG and ALSK+L-ARG groups was significantly decreased when compared with 2K1C and ALSK groups. In conclusion, combined ALSK+L-ARG treatment normalizes SBP and prevents ventricular hypertrophy in 2K1C hypertensive rats, an effect that can be partially attributed to increased baroreflex sensitivity and decreases oxidative stress.